Comparison of the Efficacy of Jilo Animation Approach versus Conventional Tell-Show-Do (TSD) Technique on Cooperation and Anxiety Levels of Children during Dental Practice: A Randomized Controlled Clinical Trials - Rasoul Sahebalam; Reihane Rafieinezhad; Marzie Boskabady (Shiraz University of Medical Sciences, 2020)
Statement of the Problem: Modeling is one of the non-pharmacological approaches to manage anxiety behavior and encourage children's cooperation in dentistry. This method is based on social learning theory in which the children learn the skills of overcoming anxiety and adapting their skills and behaviors during dental treatment. Purpose: The aim of this study was to evaluate the effect of an animated-movie modeling approach, named Jilo, on cooperation and anxiety of children in comparison with the conventional Tell-Show-Do (TSD) method in a dental setting. Materials and Method: In this randomized controlled trial, 50 healthy children (aged 4-6) with no history of dental treatment were recruited and randomly allocated to experimental (n= 24) and control (n= 24) groups. During the first visit, the experimental group watched the Jilo animated movie. After a 30-minute break, they received prophylaxis followed by fluoride therapy. The control group received the conventional TSD technique and then underwent prophylaxis and fluoride therapy. One week later, a dental restoration, which required mandibular nerve block anesthesia, was performed for both groups. The cooperation and anxiety levels of patients were evaluated during two visits using Venham Clinical Cooperation Scale (VCCS) and Venham Clinical Anxiety Scale (VCAS). Results: The mean VCAS in the experimental group was significantly lower compared to the control group during the first and second visits (p= 0.008 and p= 0.044, respectively). The mean VCCS was also significantly lower in the experimental group during the first (p= 0.015) and second visits (p= 0.019) compared to the control group. Conclusion: The application of animated-movie modeling (Jilo) can be recommended as an effective method for preparation of children before the dental treatment session.